(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The Constitution of India is an instrument that provides for a federal set-up in the country and also specifies definite functions for central and state government. The jurisdiction of central and state government with regard to the law-making process has been explicitly mentioned in Schedule 7 of the Constitution. However, there are certain circumstances through which the central government can enter the jurisdiction of states and the Presidential proclamation of emergency is one of them. The President of India can overtake the legislative and executive power of the state by imposing the emergency in a state in case of “failure of Constitutional machinery”. Article 356 states that “If the President, on receipt of report from the Governor of the State or otherwise, is satisfied that a situation has arisen in which the government of the State cannot be carried on in accordance with the provisions of this Constitution, the President may be proclaim emergency in a state”. With the proclamation of President’s Rule in a state, the elected government is dismissed and legislative assembly got suspended and the administration of the state is directly controlled by the President through his representative governor. Normally President’s Rule in a State should be proclaimed on the basis of Governor’s report under Article 356(1). The Governor’s report should be a ’speaking document,’ containing a precise and clear statement of all material facts and grounds, on the basis of which the President may satisfy himself, as to the existence or otherwise of the situation contemplated in Article 356. Since its inception, Article 356 has been a matter of debate and discussion because the President’s rule has a probability of hampering the federal structure of the nation. The origin of Article 356 can be traced back to Section 93 of the Government of India Act that provided the same provision of imposing emergency by the governor in case the province can’t be run in accordance with provisions of the act. This section was incorporated in the Indian Constitution by replacing ‘governor’ with ‘President’. However, various members of the Constitutional assembly had opposed this provision of imposing President’s Rule in a state citing the reason that Article 356 may result in union dominance over the state because of the vague and subjective nature of the word ‘otherwise’.